Somatic embryogenesis and plant regeneration from zygotic embryo-derived callus cultures of allium altaicum pall. - М Zavzandulam; B, Buyanchimeg; V, Enkhchimeg (Mongolian Journal of Agricultural Sciences, 2018)
Altain onion (Allium altaicum Pall.) grows wildly under different ecological conditions and one of the listed rare plant in Red Data Book of Mongolia. Allium altaicum pall belong to a member of the onion family (Alliaceae) and has been used for both culinary and traditional medicine and a perennial herb.The purpose of this research is to get micropropogated plants in in vitro condition from Mongolian the Allium altaicum Pall tissue culture. Allium altaicum Pall. regeneration from zygotic embryo was 70% in MS medium with 0.5 mg/l 1-Naphthaleneacetic acid, 0.2 mg/l kinetin compare to control. Convenient condition for primary callus induction observed in MS medium with 1 mg/l 2,4-dichlorophenoxyacetic acid, 0.6 mg/l 6-benzylaminopurine, 2mg/l glycine by 50.4%. Regeneration of callus induction was 61.3% and somatic embryos formed plantlets on regeneration 0.1 мг/л 2,4-D 0.1 mg/l 2,4-dichlorophenoxyacetic acid, 1 мг/л BAP 1 mg/l 6-benzylaminopurine.